Agriculture on the menu - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
In Jamaica, if we eat what we grow and grow what we eat, then the Ministry of Agriculture's mandate of providing access to safe, nutritious foods for our people would be greatly advanced.